Construction d’églises et affirmation identitaire. - Méropi Anastassiadou-Dumont (Revue des Mondes Musulmans et de la Méditerranée)
The Greek orthodox community of Pera (Beyoğlu or Stavrodromi, Istanbul), which went through a remarkable development during the last decades of the Ottoman era, is officially founded in 1804. The same year was also inaugurated the first orthodox church in Beyoğlu. This study presents the community’s progressive settlement in this part of the city, in particular through the building of the three churches opened in 1804, 1861 and 1880. The cases under study make clear that for this population – most of them immigrants – the building of places of worship was of crucial importance, especially regarding to its identity but also its place within the constantinopolitan society of this period.